ASSOCIATION BETWEEN TRIGLYCERIDE SERUM LEVELS AND GLOMERULAR FILTRATION RATE (eGFR) IN PATIENTS WITH CHRONIC RENAL FAILURE AT JEMURSARI ISLAMIC HOSPITAL SURABAYA, INDONESIA - Uswatun Hasanah; Suhariyadi; Andreas Putro Ragil Santoso (Universitas Nahdlatul Ulama Surabaya, 2020)
Chronic Renal Failure (CRF) is a progressive and irreversible decrease in kidney function. One risk factor that affects the progression of CRF is dyslipidemia due to abnormalities of lipid metabolisms. Dyslipidemia is characterized by the increase level of total cholesterol, LDL cholesterol, triglycerides, and a decrease in HDL cholesterol level. eGFR is a parameter for assessing the excretion function, by calculating the amount of filtrate produced by the renal glomerulus. This study aims to determine the relationship between serum triglyceride levels with eGFR in patient suffering from CRF at Jemursari Islamic Hospital Surabaya. This type of research is descriptive experimental with cross–sectional design. The study population was the patients with CRF. The primary data in this study was the results of examination of serum triglyceride levels in patients with CRF. The secondary data (serum creatinine levels, body weight, age, and sex) was obtained from medical records of CRF patients in February 2019. As much as 12% of patients were in the 40–50 years old category, 36% of patients were 51–60 years old, 44% of patients were 61–70 years old, and 8% of patients were 71–80 years old. 72% of patients were male. The mean triglyceride level was 146.68 mg/dL and the average eGFR was 19.86 mL/min/1.73m2. The relationships between triglyceride levels and eGFR was carried out by the Spearman–rho test where r value was –0.442 and value was 0.027. It was concluded that there was a significant negative correlation between serum triglyceride levels and eGFR in patients with CRF.